Refractive Index of Ternary Liquid Mixtures of Toluene, Cyclohexane, Carbon Tetrachloride and Benzene at 298.15 K - Krishna, V.; Agarwal, N.; Vyas, V. (Asian Journal of Chemistry, 2010)
Refractive index values of two ternary liquid mixtures: toluene+cyclohexane+carbon tetrachloride(I) and toluene+cyclohexane+benzene(II) at 298.15ºK have been measured experimentally. A comparative study to check the validity, merits and demerits of the five mixing rules viz., Lorentz, Lorenz, Gladsone-Dale, Weiner, Heller and Arago-Biot relations have been made after analysing the experimental refractive indices data for these ternary liquid mixtures.